Sprache und Recht - Haß-Zumkehr, Ulrike (Jahrbuch des Instituts für Deutsche Sprache, 2002)
This volume presents a collection of contributions by linguists and lawyers on topical questions of the interconnections between language and law, and opens up a wide range of theoretical, methodological and practical approaches to aspects such as politics and the public domain, court proceedings, criminology, the editing of legislation, legal training, and the Europeanisation of law.